Gender Communication Strategies for Women’s Empowerment: Evidence from Community Programs in Indonesia - Elis Yulianti; Harys Kristanto; Hilda Sri Rahayu; Yolandita Angga Reza; Wahyu Kurniawan (INJECT (Interdisciplinary Journal of Communication), 2025)
This research examines the importance of gender communication within the Program for Enhancing the Role of Women toward Healthy and Prosperous Families (P2WKSS) in Karangsatu Village, Bekasi. This program is a key effort aimed at empowering women and reducing poverty. Using the Delphi Method, the study involved a group of experts and community members through three repeated rounds to pinpoint, improve, and reach an agreement on the key components of the program. The results show that P2WKSS has effectively changed women's roles from being home caregivers to becoming economic participants, business owners, and decision-makers, which in turn has positively impacted local development. Effective methods of communication—utilizing face-to-face persuasion, casual meetings, and digital tools like WhatsApp—were identified as vital in promoting inclusivity and building trust, even though cultural and language obstacles persist. Symbolic resources such as uniforms, memberships in cooperatives, and stories of success acted as motivating instruments that strengthened women's identities and their ability to work together. Recognizing gender sensitivity, health programs, and collaboration among various stakeholders were found to be essential for the ongoing success of the program. The research results indicate that P2WKSS is not just a project focused on welfare; rather, it is a comprehensive empowerment system. This shows that empowering women, when integrated with communication, governance, and local economic structures, can lead to significant and lasting social change.